Chronic Kidney Disease in Liver Transplant Candidates: A Rising Burden Impacting Post–Liver Transplant Outcomes. Issue 4 (18th March 2020) - Cullaro, Giuseppe; Verna, Elizabeth C.; Lee, Brian P.; Lai, Jennifer C.
Abstract : The burden of chronic kidney disease (CKD) is rising among patients with cirrhosis, though it is not known what impact this has had on outcomes after liver transplantation (LT). All patients listed for LT in the United States between 2002 and 2017 were analyzed, excluding those listed with Model for End‐Stage Liver Disease (MELD) exceptions. The primary outcome was post‐LT mortality. We defined pre‐LT CKD as an estimated glomerular filtration rate <60 mL/minute for 90 days or ≥42 days of hemodialysis. Cox regression determined the association between pre‐LT CKD and post‐LT mortality. Of 78, 640 LT candidates, the proportion with CKD among LT recipients increased from 7.8% in 2002 to 14.6% in 2017 (test for trend, P  < 0.001). Among the 39, 719 LT recipients, pre‐LT CKD was significantly associated with post‐LT mortality (hazard ratio [HR], 1.16; P  < 0.001) even after adjusting for donor risk index (DRI), age, MELD, etiology, hepatic encephalopathy, simultaneous liver‐kidney transplantation (SLKT), and diabetes. There was no mediating influence of SLKT on the effect of pre‐LT CKD on post‐LT survival ( P  > 0.05). Therefore, pre‐LT CKD has a deleterious impact on post‐LT outcomes, which is an impact that is not mediated through SLKT. These findings highlight the need for the identification of CKD when preventative measures are possible.